2021
DOI: 10.3390/agronomy11112293
|View full text |Cite
|
Sign up to set email alerts
|

Preharvest Treatment of Methyl Jasmonate and Salicylic Acid Increase the Yield, Antioxidant Activity and GABA Content of Tomato

Abstract: This study investigated the effect of preharvest treatment of 0.25 mM methyl jasmonate (MeJA) and 0.5 mM salicylic acid (SA) on quality parameters, most important secondary metabolites (lycopene, β-carotene, ascorbic acid, total phenolics, and flavonoids), antioxidant activities, and amino acid contents of ‘Kumato’ tomato. Treatments with MeJA and SA led to an increase of total yield per plant and were effective in maintaining the fruit quality attributes such as firmness, total soluble solids, titratable acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 45 publications
1
7
1
Order By: Relevance
“…In our study, we found that MeJA had no significant effect on the fresh and dry weights of Chinese chives (Figures 1A,C). Our results contradict the findings of Baek et al (2021), who reported that MeJA treatment increased biomass in tomatoes. However, Kurowska et al (2020) showed that the application of MeJA significantly reduced the first leaf sheath and dry leaf weight of barley seedlings.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, we found that MeJA had no significant effect on the fresh and dry weights of Chinese chives (Figures 1A,C). Our results contradict the findings of Baek et al (2021), who reported that MeJA treatment increased biomass in tomatoes. However, Kurowska et al (2020) showed that the application of MeJA significantly reduced the first leaf sheath and dry leaf weight of barley seedlings.…”
Section: Discussioncontrasting
confidence: 99%
“…In sweet cherry, MeSa at 1 or 2 mM also increased TSS and TA concentration [13]. TSS is a significant harvest criterion for pitahaya fruits, and the present results revealed that MeSa at 10 mM advanced the ripening process, while harvest could be delayed with OA at 1 mM and MeJa at 5 mM, in agreement with the results reported in table grape [19] and sweet cherry [37], in which MeJa also showed lower TSS levels than control [32], and was confirmed by the higher TA content of those treated pitahayas. For this parameter, all SA treatments induced a higher percentage of TA, which was unaffected in the remained treated-pitahaya.…”
Section: Discussionsupporting
confidence: 91%
“…Lower concentrations of MeJa (at 1, 0.1, and 0.01 mM) confirmed the acceleration of the ripening process, the highest yield being maximum with MeJa at 0.01 mM. On the contrary, MeJa treatments did not affect the fruit mass and size on sweet cherry [32], probably due to that one single treatment performed at the late growth period, specifically before harvest. It is well known that a delay in harvest causes a net increase in fruit weight, as reported for 2 mM MeJa applied to sweet cherry 1 week before harvesting, but failed if applications were made 2 or 3 weeks earlier [33].…”
Section: Discussionmentioning
confidence: 76%
“…MYC2 participates in the AsA-GSH cycle and regulates the cold tolerance of tomato fruit by regulating the accumulation of AsA [142]. Treatment with 0.25 mM MeJA can significantly increase 'Kumato' tomato fruit yield and AsA content [143]. The treatment of pomegranate and blueberry fruits with MeJA can also increase the AsA content and total antioxidant activity in the fruits and improve the fruits' antioxidant capacity and storage stability [144,145].…”
Section: Effects Of Hormones On the Ascorbic Acid Accumulation In Fruitsmentioning
confidence: 99%